TEKNIK ONE SHOT DAN PEWARNAAN KONTRAS DALAM PENATAAN KAMERATELEVISI KREATIF - Suroko, Arif Pujo; Caturriyanto, Setyo Tohari (Capture : Jurnal Seni Media Rekam, 2012)
There are several television programs format,including the drama and non-drama.Videoclip is not drama or non-drama or journalism.However,video clips and commercials is a part ofa television program. Creative television is the format of audio-visual works that consist ofvideo clips and commercials. In making the creative television programs should be requiredcreative ideas for producing a visual work that is interesting and innovative.Video clip (musicvideo) is a tool for music producers to market a product or its artists through the medium oftelevision.So video clips can be defined as audiovisual works from a song produced by a group ofmusic in order to promote or popularize the music group along with their songs.Advertising isany forms of communication that is intended to motivate someone of potential buyers andsellers to promote a product or service.Advertising as a media campaign is divided into severalcategories,including:TV Commercial and Non-commercial ads.Commercial ads are advertisingthat aim to support the marketing campaign of a product or service. Meanwhile, noncommercial ads are ads in the form of a social marketing campaign to sell the idea or ideas forthe benefit or public service.Director of photography has an important role in determining thevisual concept. Changes of the script into a visual form is through the role of a camera personthinking through the medium of the camera.The use of One Shot shooting technique and colorcontrast are a visual concept that is applied in making this work.The One Shot technique is usedin the manufacture of video clips,while the contrasting coloring is applied in the manufacture ofadvertising is also on the video clip.With the visual concept is expected to give an idea of the feelof the new visualization mainly to the appreciation of communicative media are experimentaland educational, so as to form a pattern of thinking creatively in generating ideas artvisualization.Keywords :One Shot technique, color contrast, video clip, and creative television